2014
DOI: 10.1111/psyg.12059
|View full text |Cite
|
Sign up to set email alerts
|

Emotional function in dementia patients

Abstract: Behavioural and psychological symptoms of dementia, which can be considered as hyperreactivity of the emotional functioning of dementia, can be alleviated or aggravated by the behavioural and psychological symptoms of the caregiver. Comfortable stimulations of emotional function through sensory stimulations are effective methods for alleviating behavioural and psychological symptoms of dementia. Although cognitive function deteriorates with age, emotional function is often retained even in advanced years. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 82 publications
(126 reference statements)
1
26
0
3
Order By: Relevance
“…1 Similarly, caregiver distress can exacerbate BPSD and family discord or altered communication in the family need to be assessed. 79,80 …”
Section: Etiopathogenesis Of Bpsdmentioning
confidence: 99%
“…1 Similarly, caregiver distress can exacerbate BPSD and family discord or altered communication in the family need to be assessed. 79,80 …”
Section: Etiopathogenesis Of Bpsdmentioning
confidence: 99%
“…Unknown backgrounds (13%) were the backgrounds such as inactivity after retirement, removal to a new house, and/or diabetes mellitus in the similar way as a commonality of patients would have some vague backgrounds [2]. Any sickness including brain diseases as well as psychotic depressions might cause dementia with depression [3] and cause some individuals to be more sensitive to the attitude of families, as their reasonable suppression by cognitive functions decline [4], which in turn could lead to agitation and violence [5]. Although CSDD suggested that a certain number of patients were suffering from major depression, we could not estimate the depressive state in other patients because Geriatric Depression Scale is an inappropriate measure in patients with dementia.…”
Section: Csdd >10mentioning
confidence: 99%
“…Attachment may be implicated in agitation in BPSD [41,42]. For example, exhaustion of relatives may influence agitation reactions and BPSD [43], as well as separation issues. Indeed, the Subject's attachment ("Being at World") is a dynamic co-constitution from the other (between two subjects).…”
Section: Unbearable Situation and Separation's Phenomenologymentioning
confidence: 99%